A comparative study of lateral SiCN/porous silicon and vertical SiCN/porous silicon junctions for sensing ultraviolet light. (December 2015) - Chou, Tse-Heng
Highlights: The SiCN/PS heterojunction was developed for low cost UV detecting applications. The SiCN film was deposited on PS substrates with RTCVD. The PS layer suppresses the dark current to obtain a high PDCR. Abstract: In this paper, we report the comparative study of both lateral n-SiCN/p-porous silicon (PS) and vertical n-SiCN/p-porous silicon (PS) heterojunctions for low cost and high temperature ultraviolet (UV) detecting applications. The cubic crystalline n-SiCN films were deposited on p-(1 0 0) PS substrate with rapid thermal chemical vapor deposition (RTCVD). Owing to the PS layer features high resistivity and the flexibility, thus suppress the dark current to obtain a high photocurrent/dark current ratio (PDCR). Therefore, these junctions on PS substrate have achieved high sensing performances. For example, with a 0.5 mW/cm 2 sensing area and under the condition of room temperature and −5 V bias, the measured PDCR of the lateral n-SiCN/p-PS and vertical n-SiCN/p-PS heterojunctions with and without irradiation of 254 nm UV light, are up to 98.3 and 85.4, respectively. Even at the high temperature of 200 °C, they still have PDCR of 8.5 and 7.42, respectively. These values are better than that of the reported ZnO on GaAs substrate or β-SiC on Si substrate without porous treatment UV detectors.